THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, FINANSIAL PERFORMANCE AND PROFITABILITY ON FIRM VALUE OF FOOD AND BEVERAGE SECTOR COMPANIES LISTED ON THE BEI 2020-2023 - Rahmawati , Fadilla; Hariyanto, Wiwit (Journal of Economic and Economic Policy, 2024)
General Background: The role of Good Corporate Governance (GCG), financial performance, and profitability is increasingly recognized in determining firm value, particularly in sectors with substantial consumer impact, such as food and beverage. Specific Background: This study evaluates managerial ownership, financial performance using DAR, profitability using ROA, and firm value using PBV. Knowledge Gap: Despite existing literature linking these variables, there remains a limited understanding of their combined effects on firm value within the Indonesian food and beverage sector. Aims: This research aims to analyze the influence of GCG, financial performance, and profitability on the firm value of food and beverage companies listed on the Indonesia Stock Exchange (BEI) from 2020 to 2023. Results: Utilizing a purposive sampling technique, 64 companies were analyzed using multiple linear regression. The findings indicate that GCG, financial performance, and profitability all positively and significantly influence firm value, underscoring the interconnectedness of these factors. Novelty: This study contributes to the literature by providing empirical evidence within the specific context of Indonesian food and beverage firms, filling a notable gap regarding the relationships between GCG, financial performance, profitability, and firm value. Implications: The results suggest that improving GCG practices, enhancing financial performance, and maximizing profitability are critical for increasing firm value. This study offers valuable insights for investors and company management, emphasizing the importance of robust corporate governance and effective financial management to foster long-term firm value growth. Further research is recommended to explore additional variables and broader contexts.